Zodiac calendars in the Dead Sea Scrolls and their reception : ancient astronomy and astrology in early Judaism - Jacobus, Helen R. (IJS Studies in Judaica, 2015)
The ancient mathematical basis of the Aramaic calendars in the Dead Sea Scrolls is analysed in this investigation. Helen R. Jacobus re-examines an Aramaic zodiac calendar with a thunder divination text (4Q318) and the calendar from the Aramaic Astronomical Book (4Q208 - 4Q209), all from Qumran. Jacobus demonstrates that 4Q318 is an ancestor of the Jewish calendar today and that it helps us to understand 4Q208 - 4Q209. She argues that these calendars were taught in antiquity as angelic knowledge described in 1 Enoch and the Book of Jubilees . The study also encompasses Babylonian, Hellenistic, Byzantine astronomy and astrology, and classical and Jewish writings. Finally, a medieval Hebrew zodiac calendar related to 4Q318 with an astrological text is published here for the first time.